Extending contemporary decision support system designs to patient-oriented systems. - Scott, G. C. (American Medical Informatics Association, 1998)
Decision support systems for patients can benefit from adopting knowledge engineering-based architectures. In this paper, we describe how decision support systems for patients differ from decision support systems for health professionals and knowledge engineering principles that can be used to improve the efficiency of developing patient support systems. We discuss a five-step process model for patient-computer dialogue and its incorporation into an architecture based on knowledge engineering ontologies. The architecture's components are grouped into transient and persistent application layers that support a general framework for patient decision support. The implementation of the object-based model using a relational database management system is also discussed.